Eastern Caribbean Currency Union : Financial System Stability Assessment, including Report on the Observance of Standards and Codes on Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Financial System Stability Assessment on the Eastern Caribbean Currency Union (ECCU) reviews overall stability assessment. The fiscal position of the governments in the region has deteriorated sharply in recent years. A source of strength of the ECCU has been the large historical presence of strong foreign banks. However, the structure of the banking industry is changing with the entry of more aggressive regional banks, and the share of privately owned banks has increased. The limited activity of the organized ECCU securities markets reflects the small number of securities available for trading.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet